2015
DOI: 10.1016/j.pcd.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms prior to and following insulin initiation in patients with type 2 diabetes mellitus: Prevalence, risk factors and effect on physician resource utilisation

Abstract: Depressive symptoms are common with type 2 diabetes and associated with increased healthcare utilisation, reinforcing the need for holistic interdisciplinary management approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Similarly, in the literature major depressive disorder rate in patients with diabetic complications were found higher than in patients without diabetic complications. [5232526]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the literature major depressive disorder rate in patients with diabetic complications were found higher than in patients without diabetic complications. [5232526]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to beliefs about medication, emotional well‐being, including depressive symptomology and diabetes‐related distress, is associated with optimal medication‐taking behaviours. For example, depression is associated with suboptimal medication‐taking among people with type 2 diabetes prescribed OAD medications and/or insulin , and diabetes‐related distress is associated with more negative insulin perceptions . Elsewhere, a longitudinal study concluded that severity of depressive symptoms was associated with required time and number of visits with healthcare professionals for training to self‐inject, self‐adjust and manage other aspects of insulin delivery .…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…For example, depression is associated with suboptimal medication‐taking among people with type 2 diabetes prescribed OAD medications and/or insulin , and diabetes‐related distress is associated with more negative insulin perceptions . Elsewhere, a longitudinal study concluded that severity of depressive symptoms was associated with required time and number of visits with healthcare professionals for training to self‐inject, self‐adjust and manage other aspects of insulin delivery . Thus, those reporting impaired emotional well‐being may be more vulnerable to delayed medication uptake, and be more likely to have suboptimal medication‐taking behaviours.…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…In contrast to these results, other studies have found that higher depressive symptoms predict increases in HbA1c and more difficulty with self-management over time. 31,55 However one previous study examining the effect of pre-intervention depressive symptoms for people with diabetes in a lifestyle-focused weight loss intervention showed that participants at all levels of baseline depressive symptoms lost similar amounts of weight during the intervention. 56 Two similar studies of participants in DSME/S interventions showed that changes in depressive symptoms over the course of an intervention were not correlated with changes in HbA1c over the course of the intervention.…”
Section: Discussionmentioning
confidence: 99%